2010
DOI: 10.1142/s1758825110000822
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Nanotubes as Kirchhoff Elasticas

Abstract: Under compressive loads, single-walled carbon nanotubes (SWNTs) are known to behave like cylindrical shells at small aspect ratios and undergo a shell to column transition at somewhat larger aspect ratios. At even larger aspect ratios SWNTs are capable of undergoing large elastic deformations without suffering localized plastic kinks. In this work, we show that a very long SWNT can be modeled as a Kirchhoff elastica with a small initial twist. The elastic properties of the nanotubes, required to model them as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The paragraph below presents some of the most recent findings on simulated mechanical properties of SWCNT structural systems. Agnihotri and Basu [2010] conducted an MD simulation to investigate if a very long SWCNT can be modeled as a Kirchhoff's elastica with a small initial twist. They also indicated that the post-buckling deformation of the low-dimensional structures is strongly affected by the length, diameter and chirality of the nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…The paragraph below presents some of the most recent findings on simulated mechanical properties of SWCNT structural systems. Agnihotri and Basu [2010] conducted an MD simulation to investigate if a very long SWCNT can be modeled as a Kirchhoff's elastica with a small initial twist. They also indicated that the post-buckling deformation of the low-dimensional structures is strongly affected by the length, diameter and chirality of the nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…The Kirchhoff model of elastica was developed by Agnihotri and Basu [2010] in order to study the postbuckling behavior of very long length carbon nanotubes in the case of folded and coiled configurations.…”
Section: Introductionmentioning
confidence: 99%
“…In the Type II shell model, the equilibrium equations are derived by minimizing the total potential energy of the CNT. [9][10][11][12][13][14][15] Researchers have also incorporated nonlocal e®ects in Type I continuum shell models for CNT. The nonlocal parameters for CNT are calibrated from MD simulation results.…”
Section: Introductionmentioning
confidence: 99%